ANALYSIS OF BUILDING MATERIAL PREFERENCES OF CIVIL WORKERS IN ABUJA (FUDMA JOURNAL OF SCIENCES, 2025)
Building material, as one of the elements of housing, has received a very little attention of researchers over the years in the context of preferences. Civil workers are the segment of population that have similar experiences, shared housing values and common housing requirements. Most of governments’ previous housing projects targeted to workers failed due to the lack of prior study of their housing preferences. It is therefore pertinent to understand the building material preferences of government workers. Therefore, this study seeks to assess the building material preferences of Federal civil service workers in Abuja, Nigeria. Survey method was adopted in this study, and data were collected using structured questionnaire. The population of the study was the Federal civil service workers in all the Federal Ministries in Abuja, and 2,133 sample size was gotten out of 40,884 sample frame, using Slovin formula. The respondents were sampled using simple random sampling technique, and the data collected were analysed using percentage and frequency distribution. The findings of the study shows that majority of the respondents which represents 76.4%, 65.1%, 83.2%, 82.2%, 75.3%, 50.4% and 27.4% have preference for sand-cement block, long span aluminium roofing sheet, ceramic tiles, plaster of paris (POP), paint, sliding window, and imported metal door respectively. By incorporating the findings of this study into housing policy, an affordable worker-preferred-housing can be created by government. The study recommends that further research should be conducted on the correlation between building material preferences and demographic characteristics of Federal civil service workers in Abuja.
Keywords: Building materials; Housing; Housing provisions; Housing preferences; Workers’ housing